BIM Implementation in Mall Laves Project Construction Surabaya - Arif, Moh Sofyan; Durrotun Nasihien, Ronny; Sutowijoyo, Hendro (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
Nowadays, The development of Building Information Modeling (BIM) in Indonesia is very limited, even though the existence of Building Information Modeling (BIM) is very helpful in the Indonesian construction building projects. Mall Laves Surabaya project using several Building Information Modeling (BIM) based software in terms of project management planning.Â There are Autodesk Revit, Cubicost Glodon, and Autodesk Naviswork software. The purpose of this research is to implementation Building Information Modeling (BIM) in Indonesian project development. The results are 3-dimensional modeling, volume calculations based on 3 dimensions, and project schedule simulations to provide detailed visual information.